2004
DOI: 10.1614/wt-03-098
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing to Detect Herbicide Drift on Crops

Abstract: Glyphosate and paraquat herbicide drift injury to crops may substantially reduce growth or yield. Determining the type and degree of injury is of importance to a producer. This research was conducted to determine whether remote sensing could be used to identify and quantify herbicide injury to crops. Soybean and corn plants were grown in 3.8-L pots to the five- to seven-leaf stage, at which time, applications of nonselective herbicides were made. Visual injury estimates were made, and hyperspectral reflectance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 25 publications
2
46
3
Order By: Relevance
“…As for detecting herbicide injury in crops, Henry et al . used hyperspectral data to differentiate soybean and corn plants that are treated with glyphosate and paraquate for the untreated ones.…”
Section: Introductionmentioning
confidence: 99%
“…As for detecting herbicide injury in crops, Henry et al . used hyperspectral data to differentiate soybean and corn plants that are treated with glyphosate and paraquate for the untreated ones.…”
Section: Introductionmentioning
confidence: 99%
“…Henry et al . indicated that multiple indices formulated from the band information extracted from hyperspectral reflectance could distinguish between healthy and injured soybean and corn plants to which herbicides, glyphosate and paraquat had been applied.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing methods have been developed in an attempt to detect crop injury more effectively. The methods include multispectral imaging (Thelen et al, 2004;Huang et al, 2010) and spectral reflectance measurement (Henry et al, 2004). Moreover, it would be of interest to know if measurement of narrow-banded reflectance has the capability of revealing subtle changes in canopy reflectance, which could present more useful information in detecting the onset of stress from crop injury.…”
Section: Introductionmentioning
confidence: 99%